Mechanism of aging deformation zoning of surrounding rock in deep high stress soft rock roadway based on rock creep characteristics - Jing, Wei; Liu, Shuxin; Yang, Renshu; Jing, Laiwang; Xue, Weipei (Journal of applied geophysics, 2022)
With the continuous exploitation of deep coal resources, the long-term stability control of surrounding rock of deep high stress soft rock roadway has become an urgent support problem. Because the traditional surrounding rock deformation zoning theory does not consider the creep effect of rock, it is not suitable for the support design of deep soft rock roadway, and can not ensure the long-term safe production of coal mines. This work proposes a novel four-stage strain-softening model based on rock creep characteristics, reveals the deformation zoning mechanism of surrounding rock in deep high stress soft rock roadway, and proposes the determination method of actual deep roadway surrounding rock zoning type and boundary stress. Moreover, taking Pan Yidong Coal Mine in China as an example, the feasibility and accuracy of the above theoretical method are verified by test, field monitoring and ABAQUS numerical simulation, and the influencing factors of the deformation zoning type of surrounding rock of the actual roadway are analyzed. The results show that the actual surrounding rock zoning type and boundary stress value determined by the deformation zoning mechanism of deep roadway surrounding rock in this paper are more accurate than the calculation results of the traditional deformation zoning theory, and the variations in the basic mechanical properties of surrounding rock and the strength of the in-situ stress field determined the number of actual deformation zones and the boundary stress values of each zone in the roadway surrounding rock. The research results can potentially aid the support designing and stability evaluation of deep roadway surrounding rock. •Actual deformation zones in deep roadway surrounding rock were analyzed.•Novel four-stage strain-softening model determines zoning type and boundary stress.•Factors influencing the type and number of deformation zones were investigated.•Actual deformation zones rely on mechanical properties and in-situ stress of rock.•Model accuracy was verified using field tests and numerical simulations.